2020
DOI: 10.3389/fmars.2020.00496
|View full text |Cite
|
Sign up to set email alerts
|

Movement of Microphytobenthos and Sediment Between Mudflats and Salt Marsh During Spring Tides

Abstract: The movement of sediment and associated microphytobenthos (MPB) between the upper mudflat and salt marsh in a macrotidal estuary was investigated by comparing the variability of benthic chlorophyll a (Chl. a) and suspended Chl. a during flood and ebb spring tides during the 2015 supermoon event. Sampling was carried out for 4 days in August and September. Flood-tide water carried significantly higher amounts of Chl. a from the mudflat transition zone onto the salt marsh compared to the amount of leaving the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Furthermore, the concentration of 20:5ω3,6,9,12,15 in the PZ strongly exceeded that in the LSM and PZ indicating high abundance of diatoms. Given the importance of diatoms in the stabilization of tidal flat sediments (Holland et al, 1974 ; Hope et al, 2020 ) and their addition to salt marsh soils with the tide (Redzuan & Underwood, 2020 ; Scholz & Liebezeit, 2012a ), their high abundance in the PZ underlines their key role in frequently inundated salt marsh zones. The reduced presence of 20:5ω3,6,9,12,15 in the LSM and USM likely reflects a shift toward the dominance of heterotrophic microorganisms at higher elevation in the salt marsh.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the concentration of 20:5ω3,6,9,12,15 in the PZ strongly exceeded that in the LSM and PZ indicating high abundance of diatoms. Given the importance of diatoms in the stabilization of tidal flat sediments (Holland et al, 1974 ; Hope et al, 2020 ) and their addition to salt marsh soils with the tide (Redzuan & Underwood, 2020 ; Scholz & Liebezeit, 2012a ), their high abundance in the PZ underlines their key role in frequently inundated salt marsh zones. The reduced presence of 20:5ω3,6,9,12,15 in the LSM and USM likely reflects a shift toward the dominance of heterotrophic microorganisms at higher elevation in the salt marsh.…”
Section: Discussionmentioning
confidence: 99%
“…The functioning of salt marshes as carbon sinks results from slow decomposition of highly productive, lignocellulose‐rich terrestrial plants by microbial communities (Hemminga & Buth, 1991 ; Hemminga et al, 1988 ; Leadbeater et al, 2021 ). In addition, inundation of the salt marsh brings allochthonous marine material, such as algal wrack and microphytobenthos, to the marsh adding to the autochthonous organic matter input to the system (Polis & Hurd, 1996 ; Redzuan & Underwood, 2020 ; Zong & Horton, 1998 ). Recent studies indicated the use of these marine resources by soil mesofauna of the salt marsh (Haynert et al, 2017 ; Winter et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…This natural low-light acclimation seems particularly useful in macrotidal estuaries, which have very turbid waters, and may partly explain their success in the Loire Estuary polyhaline reaches. By moving from the pelagic to the benthic environment, they prolong their stay in estuarine intertidal areas, where nutrient conditions are favourable (Sabbe et al 2010), while using the tidal resuspension cycles as a dispersion mechanism (Redzuan & Underwood 2020). Contrary to the epipelon, tychoplanktonic diatoms cannot vertically migrate to the sediment surface during low tides (Consalvey et al 2004).…”
Section: Comparison With Other European Estuariesmentioning
confidence: 99%
“…Mesocosm approaches allow for controlled experimental manipulation of intact intertidal sediment communities while maintaining as close as possible natural environmental conditions. 54,55,109,110 The impact of grazing fish 111 and wave action on biofilm resuspension 112 were not simulated, but our approach simulated important environmental drivers of sedimentbiofilm ecology: tidal cover, natural daylight quality and periodicities, rainfall, temperature, and nutrient resupply. Microphytobenthic activity (Chl a : phaeophytin ratio, F v /F m ) indicated healthy biofilm functioning was sustained throughout the experimental periods, permitting conclusions about the environmental impacts of addition of NPs on biofilm related ecosystem functions to be drawn.…”
Section: Environmental Impact Of Titanium Oxide Nanoparticlesmentioning
confidence: 99%
“…114 By reducing the colloidal carbohydrate content of microphytobenthic biofilms, TiO 2 -NPs have a potentially significant environmental effect in reducing biostabilisation of sediment, leading to increased resuspension of biofilms and sediment in sheltered estuaries by wind driven waves. 112 Coastal sediment protection through biostabilisation is an important ecosystem service provided by microbial biofilm, 31 as coastal erosion has been estimated to cost about 500 million dollars per year in the US only. 115 In our experiments, NPs had no effect on biofilm photosynthetic maximum potential (F v /F m ), or respiration, but a short-term negative influence of TiO 2 -NPs on net primary production was observed in winter.…”
Section: Environmental Impact Of Titanium Oxide Nanoparticlesmentioning
confidence: 99%